An Invitation to Transformation: The Importance of Cate Hundleby’s Work to Contemporary Scientific Epistemology - Meynell, Letitia (Informal Logic, 2026)
In this paper, I examine how Cate Hundleby’s work in feminist standpoint epistemology and feminist argumentation theory might shore up Helen Longino’s contextual empiricism and offer suggestions as to its effective application. I show how, despite the complexities of intersectionality and shifting power relations, feminist standpoint theory offers useful suggestions for scientific practice, particularly the inclusion of marginalized voices throughout the scientific process. I then show how feminist argumentation theory provides insight into the challenges of meeting the ‘tempered equality of epistemic authority’ that Longino requires as well as approaches to argumentation that might better serve this goal.